First Evidence for Multiple‐Harmonic Standing Alfvén Waves in Jupiter's Equatorial Plasma Sheet - H. Manners; A. Masters (Geophysical Research Letters)
Abstract Quasiperiodic pulsations in the ultralow‐frequency band are ubiquitously observed in the Jovian magnetosphere, but their source and distribution have until now been a mystery. Standing Alfvén waves on magnetic field lines have been proposed to explain these pulsations and their large range in observed periods. However, in situ evidence in support of this mechanism has been scarce. Here we use magnetometer data from the Galileo spacecraft to report first evidence of a multiple‐harmonic ultralow‐frequency event in Jupiter's equatorial plasma sheet. The harmonic periods lie in the 4‐ to 22‐min range, and the nodal structure is confined to the plasma sheet. Polarization analysis reveals several elliptically polarized odd harmonics and no presence of even harmonics. The harmonic periods, their polarization, and the confinement of the wave to the plasma sheet are strong evidence supporting the standing Alfvén wave model. Multiple‐harmonic waves therefore potentially explain the full range of periods in quasiperiodic pulsations in Jupiter's magnetosphere.